MENINGKATKAN KREATIVITAS BELAJAR SISWA PADA TEMA PERISTIWA DALAM KEHIDUPAN DENGAN MENGGUNAKAN MODEL PEMBELAJARAN WORD SQUARE DI KELAS V SDN 104204 SAMBIREJO TIMUR T.A 2020/2021 - Yusmilana; Wiwik Lestari; Thessa Herdyana (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2022)
The problem studied in this study is the low creativity of students in social studies subject matter in class V SDN 10420 Sambirejo Timur. This study aims to determine whether using the Mind Word Square learning method can improve student learning creativity in social studies subjects, the material of the role of struggle figures. The subjects in this study were all fifth grade students of SDN 104204 Sambirejo Timur, totaling 37 students consisting of 21 male students and 16 female students.. The data collection tool used is to use an observation sheet to measure the level of creativity in student learning. From the results of observations in the initial conditions, it shows that students' learning creativity is very lacking with the percentage of classical completeness only 29.8%. Furthermore, the results of this study indicate that the observation of student learning creativity during the first cycle with the average value increased to 67.55%, then increased in the second cycle to 75.20%, and at the second meeting it increased to 78.3%. While the success rate of classical learning creativity in the first cycle of meeting 1 was 22.22%, and at the second meeting it increased to 61.11%, in the second cycle of meeting 1 it increased to 89.33%. Thus, it can be concluded that the use of the Word Square method can increase student learning creativity on the subject matter of the role of the struggle shop in class V SDN 104204 Sambirejo Timur Academic Year 2020-2021. This means that the Word Square method can be used as an alternative in social studies learning.